Influence of the Thermal Treatment to Address a Better Osseointegration of Ti6Al4V Dental Implants: Histological and Histomorphometrical Study in a Rabbit Model. (27th June 2018) - Scarano, Antonio; Crocetta, Ezio; Quaranta, Alessandro; Lorusso, Felice
Abstract : Background . Pure titanium continues to be the first choice for dental implants and represents the gold standard for their biocompatibility and physical and mechanical characteristics, while the titanium alloy (Ti6Al4V) has good mechanical properties. The surface structure of the titanium oxide layer formation on the surface influences and improves the bone response around dental implants. Purpose . The purpose of this study is to evaluate the influence of a thermal treatment of Ti6Al4V implant surfaces and the bone healing response in a rabbit model . Methods . Altogether sixteen implants with same design were inserted into the distal femoral metaphysis. A screw (13 mm long, 4 mm in diameter) was inserted in an implant bed. Each rabbit received two implants, one in the left femur and one in the right femur. The samples were histologicallyand histomorphometrically evaluated at 8 weeks . Results . A statistically significant difference (p = 0.000034) was present histologically in the percentages of bone-implant contact (BIC) between the test group (BIC = 69.25±4.49%.) and control group (BIC = 56.25 ± 4.8%) by one-way analysis of variance (ANOVA). Significance was set atp ≤ 0.05. Conclusions . The outcome of the present study indicates a novel approach to improving bone healing around titanium implants.